Cement-based composite material with friction nanometer power generation characteristic and preparation method thereof
By compounding high-dielectric constant nanomaterials in cement-based energy storage materials and using low melting point alloy/polymer composite electrode layers, the problems of low efficiency of low mechanical energy conversion and limited power generation efficiency of cement-based energy storage materials are solved, and high output performance and long-term stability are achieved.
Patent Information
- Application Number
- CN202411957255.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-29
- Publication Date
- 2025-04-04
AI Technical Summary
The existing cement-based energy storage materials have low efficiency in low frequency and low load mechanical energy conversion, and the power generation efficiency is limited by the temperature and humidity environment. The externally doped materials have a negative impact on the mechanical strength and durability of concrete, resulting in limited application.
A cement matrix with composite doping of high dielectric constant nanomaterials is used as the friction layer, and a low-melting point alloy/polymer composite material is used as the electrode layer to build a single-electrode mode nanogenerator to improve interface polarization and bonding performance.
The high output performance and long-term stability of cement-based composite materials under cyclic friction and load are achieved. The output voltage is controlled above 40V, the output current is above 120nA, and the compressive strength is maintained within 15% of the original cement.
Smart Images

Figure CN119750990A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a cement-based composite material with friction nano-power generation characteristics and a preparation method thereof. Background Art
[0002] With the vigorous development of Internet of Things technology, a large number of sensor devices and micro-nano devices have gradually emerged in infrastructure projects, bringing unprecedented efficiency to structural health monitoring and engineering intelligence. However, the huge demand for these devices has also posed new challenges to energy supply strategies. As a bulk material for infrastructure projects, cement is widely distributed in application scenarios such as transportation and construction, and has huge potential for energy collection and conversion. Compared with polymer materials, cement-based materials have the advantages of high compressive strength, excellent wear resistance, good durability, and low cost, making them highly feasible and adaptable in the research and development of energy storage materials for engineering scenarios.
[0003] At present, cement-based piezoelectric materials, thermoelectric materials, humidity power generation materials, and supercapacitors have been widely developed and have achieved good results. However, the above energy storage methods often have problems such as insensitivity to low-frequency and low-load mechanical energy, low energy conversion efficiency, or power generation efficiency is limited to temperature and humidity environmental conditions. In addition, excessive amounts of alkali or metal salt electrolytes and other external admixtures will also pose challenges to the mechanical strength and durability of concrete, greatly limiting the application and promotion of cement-based energy storage materials.
[0004] There is often a large amount of disordered, low-frequency mechanical energy in infrastructure scenes, such as wheel friction, water flow disturbance, structural vibration, etc. Taking advantage of the unique advantages of cement-based materials, a new type of friction nanogenerator can be developed to collect mechanical energy in infrastructure scenes and convert it into electrical energy, providing a reliable energy supply for various self-powered sensors, intelligent monitoring systems, etc. The combination of friction nanogenerators based on cement-based materials and self-powered sensing equipment will bring innovative changes to the infrastructure field, and its application prospects are very broad. At present, the research and development of cement-based nano-power generation materials mostly uses ordinary metal sheets as electrode layers to construct single-electrode nano-power generation devices. However, ordinary metal electrode layers usually have poor adhesion to the interface of the cement matrix, and the strain compliance of the metal electrode layer is poor, which often leads to interface cracks in cement-based nano-friction materials under the influence of reciprocating cyclic friction and load, as well as shrinkage deformation, which significantly affects the output performance, stability and durability.
[0005] To this end, the present invention is proposed based on the limitations of the above-mentioned cement-based energy storage materials, such as low energy conversion efficiency, power generation efficiency being limited by temperature and humidity stimulation, and the output performance of current cement-based friction nano-power generation materials needing to be improved and poor long-term performance stability. Summary of the invention
[0006] Based on the excellent energy conversion efficiency of nano-power generation materials for a large amount of disordered and low-frequency mechanical energy in infrastructure scenarios, the present invention provides a cement-based composite material with friction nano-power generation characteristics and a preparation method thereof. The cement-based composite material has high output performance and stable long-term performance under cyclic friction and load.
[0007] The technical solution of the present invention to achieve the above object is:
[0008] In the first aspect, the present invention provides a cement-based composite material with friction nano-power generation characteristics, including a cement matrix and an electrode layer arranged in the cement matrix, wherein the cement matrix is doped with high dielectric constant nanomaterials to form a friction layer; the electrode layer is a low melting point alloy / polymer composite material, and the electrode layer is arranged in the friction layer.
[0009] Furthermore, the addition amount of the high dielectric constant nanomaterial is 0.1%-1.5% of the cement mass;
[0010] The volume ratio of the low melting point alloy component to the polymer solution in the raw materials of the low melting point alloy / polymer composite material is 0.06-0.2.
[0011] Furthermore, the dielectric constant of the high dielectric constant nanomaterial is greater than 10, and is preferably at least one of nano titanium dioxide, nano aluminum dioxide, nano barium titanate or nano strontium titanate;
[0012] The low melting point alloy is an alloy material with a melting point of 60-90° C., preferably at least one of indium tin bismuth alloy, bismuth tin lead gallium alloy, gallium indium alloy, and bismuth tin lead indium alloy;
[0013] The polymer solution uses water as a solvent, and uses a polymer material that is soluble in water and can form a film, and a stabilizer that promotes the dispersion of a low-melting-point alloy as solutes.
[0014] Furthermore, the polymer material is at least one of polyvinyl alcohol, polyethylene glycol, polyimide, hydroxymethyl cellulose or polyacrylamide polymer materials;
[0015] The stabilizer is an N-vinylamide polymer, preferably at least one of polyvinyl pyrrolidone, poly(N-vinylamine), and poly(N-vinylacetamide);
[0016] The cement in the cement matrix is at least one of ordinary Portland cement, sulphoaluminate cement, phosphate aluminate cement, aluminate cement, phosphate cement and magnesium oxychloride cement.
[0017] Furthermore, the low melting point alloy in the low melting point alloy / polymer composite material is micro-nano-scale particles, and the low melting point alloy is wrapped with a polymer solution outside, and has a flow vibration potential SVP.
[0018] Furthermore, the raw material composition and mass percentage of the cement matrix are: 200 parts of cement, 0.2-3 parts of high dielectric constant nanomaterial, 1.6-3 parts of water reducer, and 60 parts of water;
[0019] The raw materials of the low melting point alloy / polymer composite material include a polymer solution component and a low melting point alloy component, wherein the polymer solution component is composed of 5-35 parts of polymer material, 0.05-0.2 parts of stabilizer, and 100 parts of deionized water in parts by weight;
[0020] The low melting point alloy component is added according to volume fraction, and its volume ratio to the polymer solution component is 0.06-0.2.
[0021] In a second aspect, the present invention provides a method for preparing a cement-based composite material having friction nano-power generation characteristics, the preparation method comprising the following steps:
[0022] (1) adding a polymer material to water, stirring it with a constant temperature magnetic force until it is uniformly dissolved at a dissolution temperature, and maintaining the constant temperature condition, adding a stabilizer thereto, stirring it with a magnetic force until it is uniformly dissolved, and obtaining a polymer solution; the dissolution temperature can promote the water-soluble polymer material to dissolve in water to form a uniform polymer solution;
[0023] (2) maintaining a temperature higher than the melting point of the low-melting-point alloy, adding low-melting-point alloy particles to the polymer solution, allowing the low-melting-point alloy to reach its melting point, causing it to first melt into a liquid state in the polymer solution, and then stirring at a high speed to form uniformly dispersed micro droplets, stirring at a uniform speed until the low-melting-point alloy droplets are uniformly dispersed in the polymer solution, and the low-melting-point alloy droplets are micro-nano-sized;
[0024] Subsequently, the uniformly dispersed polymer solution is allowed to stand at room temperature for a period of time. Due to hydrogen bonding between the polymer chain and the low-melting-point alloy, a state of the low-melting-point alloy droplets being coated with the polymer chain is formed, so that the low-melting-point alloy droplets coated with the polymer solution are fully precipitated, and the supernatant is removed to obtain a low-melting-point alloy / polymer composite material;
[0025] (3) pouring the low melting point alloy / polymer composite material into a sheet-shaped silica gel mold, vibrating and compacting it, and then drying it at room temperature to obtain an electrode layer material;
[0026] (4) adding the high dielectric constant nanomaterial to the cement dry powder at least twice, and mechanically stirring at a speed of 300-450 rpm / min for 2-5 minutes at room temperature to obtain a uniformly mixed dry material mixture; then adding the water reducer into the water, magnetically stirring at room temperature to make it uniform, and immediately pouring it into the dry material mixture, and then stirring it at a uniform speed for 5-10 minutes, pouring it into a plate-shaped mold, and vibrating it until it is dense to obtain a cement matrix;
[0027] (5) inserting the electrode layer material into the cement matrix so that it is located in the middle of the thickness of the cement matrix, externally connecting a copper wire, and then coating and curing at room temperature to a specified age to obtain a cement-based composite material with friction nano-power generation characteristics.
[0028] Furthermore, in step (2), the high-speed stirring speed is 3000-4000 r / min, the stirring time is 5-10 min, and the temperature is 80-100° C.;
[0029] The size of the sheet-like silicone film is: 0.5-2mm thick and 100-500mm in area. 2 ;
[0030] The curing method in step (5) is: after coating for 24 hours, the specimen is cured in a curing box at 20±2° C. and a relative humidity of 95% for up to 28 days.
[0031] In a third aspect, the present invention also protects a cement-based composite material having friction nano-power generation characteristics obtained by the above-mentioned preparation method, wherein the cement-based composite material has high output performance and stable long-term performance under cyclic friction and load.
[0032] The hydroxyl functional groups of the polymer material form hydrogen bonds with the spontaneously oxidized surface of the low-melting-point alloy, which helps to form micro-nano-scale low-melting-point alloy droplets and make them evenly dispersed, and form microchannels between the low-melting-point alloy droplets, thereby constructing the flow vibration potential SVP model;
[0033] The output voltage of the cement-based composite material can be controlled above 40V, while the output current is above 120nA, and the difference in compressive strength relative to the original cement is kept within 15%.
[0034] Compared with the prior art, the present invention has the following beneficial effects:
[0035] 1. The fixed friction layer of the present invention adopts a cement matrix doped with nanomaterials with high dielectric constants. The addition of high dielectric constant nanofillers can promote interfacial polarization, so that the dielectric constant of the cement-based material increases with the increase of the nanofiller dosage, so as to optimize the energy conversion efficiency of cement-based nano-power generation.
[0036] 2. The low melting point alloy / polymer composite material of the present invention has a lower Young's modulus, excellent flexibility, elasticity and strain compliance than the traditional metal sheet electrode material, ensuring the strain sensitivity of the electrode layer to the external load; at the same time, the low melting point alloy / polymer composite material can produce hydrogen bond cross-linking with the cement hydration product, so the interface between the low melting point alloy / polymer composite electrode layer and the high dielectric constant cement matrix friction layer has excellent bonding performance, thereby ensuring that the nano power generation material has stable long-term performance under cyclic friction and load. In the embodiment, the output performance only decreases by 1.26% under 10N pressure and 8000 cycles of load. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] Figure 1 Schematic diagram of the working principle of cement-based composite materials with friction nanopower generation characteristics (a)-(d) and three-dimensional structure explosion diagram (e).
[0038] Figure 2 Schematic diagram of the working principle of laminar vibration potential (SVP) of low-melting-point alloy / polyvinyl alcohol composite electrode.
[0039] Figure 3 Photographs and interface micrographs of cement-based composite samples with friction nanopower generation characteristics after 10N pressure and 8000 cyclic loads: (a) Photograph of cement-based composite sample with friction nanopower generation characteristics prepared in Comparative Example 1; (b) Micrograph of the interface between the stainless steel electrode prepared in Comparative Example 1 and the cement matrix; (c) Photograph of cement-based composite sample with friction nanopower generation characteristics prepared in Example 3; (d) Micrograph of the interface between the electrode layer of the low-melting-point alloy / polyvinyl alcohol composite material and the cement matrix.
[0040] Figure 4 Output performance of cement-based composite materials with friction nanopower generation characteristics: (a) output voltage of the cement-based composite materials with friction nanopower generation characteristics prepared in Example 3; (b) output current of the cement-based composite materials with friction nanopower generation characteristics prepared in Example 3.
[0041] Figure 5 The output voltage of the cement-based composite material with friction nanopower generation characteristics prepared in Example 3 under cyclic contact action.
[0042] Figure 6 Graph showing the test results of the interfacial bonding performance between the low melting point alloy / polyvinyl alcohol composite material prepared in Example 3 and the cement matrix.
[0043] Figure 7 Microstructure of the low melting point alloy / polyvinyl alcohol composite material prepared in Example 3. DETAILED DESCRIPTION
[0044] The present invention is further explained below in conjunction with the embodiments and drawings, but this is not intended to limit the scope of protection of the present application.
[0045] The working principle of the present invention is: a cement matrix doped with nanomaterials with high dielectric constant is used as a fixed friction layer, a low melting point alloy / polymer composite material is used as an electrode layer, and a ground load is used to construct a single-electrode mode nanogenerator. The power generation mode of the single-electrode nanogenerator is: a car tire, a pedestrian's shoe, etc. are used as a free friction end, and the layer where the free friction end is located is called a free-end friction layer. When the free-end friction layer reciprocates with the fixed friction layer under the action of an external load, charge transfer occurs between the free-end friction layer and the fixed friction layer (cement-based friction layer), so that a potential difference is formed between the electrode layer and the ground end, thereby driving electrons to move in the external circuit (see Figure 1 ) is used to realize energy collection in multiple scenarios such as mechanical movement and wave fluctuations, and to supply power to auxiliary electrical equipment in the infrastructure engineering field.
[0046] Low melting point alloy / polymer composite material is used as the electrode layer to construct the stream vibration potential (SVP) electric layer structure of low melting point alloy particles and polymer medium. When there is no external load stimulation, the low melting point alloy particles and polymer interface generate a double electric layer and reach a charge balance state (see Figure 2 (a)); when the cement-based nanomaterials come into contact with the external free-end friction layer (such as tires, pedestrian shoes), the external load can cause the polymer material in the electrode layer to deform slightly, which in turn causes the positive charge in the polymer material to shift slightly with the movement of water molecules. At this time, a potential difference is formed between the moving positive charge and the negative charge in the low-melting-point alloy, which helps to enhance the current conversion when the free-end friction layer contacts the cement-based material; when the external load is unloaded, the electrode layer deforms back to its initial state, and the double electric layer is reconstructed (see Figure 2 (d)).
[0047] The cement-based composite material with friction nano-power generation characteristics of the present invention comprises a cement matrix and an electrode layer arranged in the cement matrix, wherein the cement matrix is doped with high dielectric constant nanomaterials to form a friction layer; the electrode layer is a low melting point alloy / polymer composite material, and the electrode layer is arranged in the friction layer.
[0048] The addition amount of the high dielectric constant nanomaterial is 0.1%-1.5% of the cement mass;
[0049] The volume ratio of the low melting point alloy component to the polymer solution in the raw materials of the low melting point alloy / polymer composite material is 0.06-0.2.
[0050] Preferably, the raw material composition and mass percentage of the cement matrix are: 200 parts of cement, 0.2-3 parts of high dielectric constant nanomaterial, 1.6-3 parts of water reducer, and 60 parts of water;
[0051] The raw materials of the low melting point alloy / polymer composite material include a polymer solution component and a low melting point alloy component, wherein the polymer solution component is composed of 5-35 parts of polymer material, 0.05-0.2 parts of stabilizer, and 100 parts of deionized water in parts by weight;
[0052] The low melting point alloy component is added according to volume fraction, and its volume ratio to the polymer solution component is 0.06-0.2.
[0053] Preferably, the high dielectric constant nanomaterial has a dielectric constant greater than 10, and is preferably one or more of nano titanium dioxide, nano aluminum dioxide, nano barium titanate, nano strontium titanate, etc.;
[0054] Preferably, the low melting point alloy is a low melting point alloy material with a melting point of 60-90°C, so that it can meet the later service conditions of cement materials. It is preferably indium tin bismuth alloy, bismuth tin lead gallium alloy, gallium indium alloy, bismuth tin lead indium alloy. The specific composition of the alloy can be determined according to the required melting point based on the existing technology.
[0055] Preferably, the polymer material is a water-soluble, film-forming polymer material, preferably at least one of polyvinyl alcohol, polyethylene glycol, polyimide, hydroxymethyl cellulose, polyacrylamide and the like.
[0056] Preferably, the stabilizer is an N-vinylamide polymer, preferably at least one of polyvinyl pyrrolidone, poly(N-vinylamine), poly(N-vinylacetamide), etc.;
[0057] Preferably, the cement material is at least one of ordinary Portland cement, sulphoaluminate cement, phosphate aluminate cement, aluminate cement, phosphate cement, magnesium oxychloride cement and the like.
[0058] The preparation method of the cement-based composite material having the characteristics of friction nano-power generation in the present invention comprises the following steps:
[0059] (1) adding a polymer material to water, stirring it with a constant temperature magnetic force until it is uniformly dissolved at a dissolution temperature, and maintaining the constant temperature condition, adding a stabilizer thereto, stirring it with a magnetic force until it is uniformly dissolved, and obtaining a polymer solution; the dissolution temperature can promote the water-soluble polymer material to dissolve in water to form a uniform polymer solution;
[0060] (2) maintaining a temperature higher than the melting point of the low-melting-point alloy, adding low-melting-point alloy particles to the polymer solution, allowing the low-melting-point alloy to reach its melting point, causing it to first melt into a liquid state in the polymer solution, and then stirring at a high speed to form uniformly dispersed micro droplets, stirring at a uniform speed until the low-melting-point alloy droplets are uniformly dispersed in the polymer solution, and the low-melting-point alloy droplets are micro-nano-sized;
[0061] Subsequently, the polymer solution in which the low-melting-point alloy is evenly dispersed is allowed to stand for a period of time at room temperature, and due to the hydrogen bonding between the polymer chain and the low-melting-point alloy, a state of the low-melting-point alloy droplets being covered by the molecular chain is formed, so that the low-melting-point alloy droplets covered with the polymer solution are fully precipitated, and the supernatant is removed to obtain a low-melting-point alloy / polymer composite material;
[0062] (3) pouring the low melting point alloy / polymer composite material into a sheet-shaped silica gel mold, vibrating and compacting it, and then drying it at room temperature to obtain an electrode layer material;
[0063] (4) adding the high dielectric constant nanomaterial to the cement dry powder at least twice, and mechanically stirring at a speed of 300-450 rpm / min for 2-5 minutes at room temperature to obtain a uniformly mixed dry material mixture; then adding the water reducer into the water, magnetically stirring at room temperature to make it uniform, and immediately pouring it into the dry material mixture, and then stirring it at a uniform speed for 5-10 minutes, pouring it into a plate-shaped mold, and vibrating it until it is dense to obtain a cement matrix;
[0064] (5) inserting the electrode layer material into the cement matrix so that it is located in the middle of the thickness of the cement matrix, externally connecting a copper wire, and then coating and curing at room temperature to a specified age to obtain a cement-based composite material with friction nano-power generation characteristics.
[0065] In the present invention, the stabilizer has excellent water solubility, can be quickly dissolved in water, and can significantly reduce the surface tension of the low melting point alloy droplets, which helps it to be better dispersed in the polymer solution. There is hydrogen bond crosslinking between the polymer chain and the cement, so that the electrode layer material has good flexibility. In addition, hydrogen bond crosslinking can be generated between the electrode layer and the cement hydration product, thereby significantly improving the interfacial bonding performance between the electrode layer and the cement-based fixed friction layer. When an external load acts on a cement-based composite material with friction nano-power generation characteristics, the electrode layer has excellent strain compliance and can adapt to the slight deformation of the cement matrix. Its good interface connection avoids the peeling problem between the cement and the electrode layer, which leads to a significant reduction in the overall bearing capacity and electrical output performance of the material. At the same time, adding high dielectric constant nanomaterials of suitable components to the cement matrix can improve dielectric properties, improve its energy conversion efficiency, and thus improve overall output performance. In addition, nanomaterials can also play a size filling effect and a heterogeneous nucleation effect to enhance the mechanical properties of cement-based materials.
[0066] The amount of low melting point alloy added in the present invention ensures that it can be fully wrapped in the polymer solution. Setting a temperature higher than the melting point of the low melting point alloy can cause the low melting point alloy to undergo a phase change from solid to liquid. Further, under high-speed stirring, the low melting point metal alloy can be evenly dispersed into micron-sized droplets in the organic solution to construct a stream vibration potential (SVP) structure.
[0067] In the step (2), the high-speed stirring speed is 3000-4000 r / min, the stirring time is 5-10 min, the temperature is 80-100° C., and the preferred temperature is 90° C., which is much higher than the melting point of the low-melting-point alloy and is controlled below the boiling point of water.
[0068] The thickness and area of the low melting point alloy / polymer composite electrode layer of the present invention will affect the output voltage and current, and the output efficiency gradually increases with the increase of the contact area and thickness. The thickness and area of the electrode layer are not limited to the scope of the present invention, and the thickness and area size of the cement-based composite material are not limited to the scope of the present invention.
[0069] Example 1
[0070] The preparation process of the cement-based composite material with friction nano-power generation characteristics in this embodiment is:
[0071] (1) Add 10 parts of polyvinyl alcohol to deionized water, and stir the mixture with a magnetic stirrer at a constant temperature of 90° C. until the mixture is uniformly dissolved, thereby obtaining a polyvinyl alcohol solution. Keep the constant temperature at 90° C., add 0.1 parts of polyvinyl pyrrolidone to the polyvinyl alcohol solution, and stir the mixture with a magnetic stirrer until the mixture is uniformly dissolved, thereby obtaining a polyvinyl alcohol / polyvinyl pyrrolidone mixed solution.
[0072] (2) maintaining a constant temperature of 90° C., adding indium tin bismuth alloy particles (melting point of 60° C.) with a volume fraction of 0.1 of the polyvinyl alcohol / polyvinyl pyrrolidone mixed solution to the polyvinyl alcohol / polyvinyl pyrrolidone mixed solution, and stirring the mixture at a speed of 3000 r / min for 10 min using a high-speed stirrer to uniformly disperse low-melting-point alloy droplets in the polyvinyl alcohol / polyvinyl pyrrolidone mixed solution, wherein the size of the low-melting-point alloy droplets is about 100 μm;
[0073] The mixed solution was then left to stand for 8 hours. Due to hydrogen bonding between the polymer chains and the low-melting-point alloy, the molecular chains enveloped the low-melting-point alloy droplets, allowing the low-melting-point alloy droplets enveloped by the polymer solution to fully precipitate. The supernatant was removed to obtain a low-melting-point alloy / polyvinyl alcohol composite material.
[0074] (3) Pour the low melting point alloy / polymer composite material into a 1 mm thick and 200 mm area 2 The material was placed in a sheet-shaped silica gel mold, vibrated and compacted, and then dried at room temperature for 12 hours to obtain the electrode layer material.
[0075] (4) 0.4 parts of nano titanium dioxide were added to ordinary silicate P·I 52.5 cement powder in three times, and mechanically stirred at 400 rpm / min for 5 minutes at room temperature to obtain a uniformly mixed dry material mixture. 1.6 parts of water reducer were added to 60 parts of water, and magnetically stirred at 300 rpm for 3 minutes at room temperature, and then immediately poured into the dry material mixture, mechanically stirred at a uniform speed for 5 minutes, poured into a 40 mm*40 mm*10 mm plate mold, and vibrated until dense to obtain a cement matrix.
[0076] (5) Inserting the electrode layer material into the cement matrix so that it is located in the middle of the thickness of the cement matrix and externally connected to a copper wire. Then, after coating at room temperature for 24 hours, the specimen is cured in a curing box at 20±2°C and a relative humidity of 95% for 28 days to obtain a cement-based composite material with friction nano-power generation characteristics.
[0077] Example 2
[0078] The difference between this embodiment and embodiment 1 is that 30 parts of polyvinyl alcohol are weighed and added into deionized water, and the polyvinyl alcohol solution is obtained by constant temperature magnetic stirring at 90° C. until the polyvinyl alcohol solution is uniformly dissolved. The rest is the same as that in embodiment 1.
[0079] Example 3
[0080] The difference between this embodiment and embodiment 1 is that 25 parts of polyvinyl alcohol are weighed and added into deionized water, and the polyvinyl alcohol solution is obtained by constant temperature magnetic stirring at 90° C. until the polyvinyl alcohol solution is uniformly dissolved. The rest is the same as that in embodiment 1.
[0081] Figure 4 Output performance of cement-based composite materials with friction nanopower generation characteristics: (a) output voltage of cement-based composite materials with friction nanopower generation characteristics; (b) output current of cement-based composite materials with friction nanopower generation characteristics, achieving stable output of voltage and current.
[0082] Figure 5 The output voltage of the cement-based composite material with friction nano-power generation characteristics prepared in this embodiment under cyclic contact only decreased by 1.26% under 10N pressure and 8000 cycles of load. Therefore, the interface between the low-melting-point alloy / polymer composite electrode layer and the cement-based friction layer has excellent bonding performance, thereby ensuring that the nano-power generation material has stable long-term performance under cyclic friction and load.
[0083] Figure 6The results of the test of the interfacial bonding performance between the low melting point alloy / polyvinyl alcohol composite material prepared in this embodiment and the cement matrix are shown in the figure. The interface between the low melting point alloy / polymer composite electrode layer and the cement matrix friction layer has excellent bonding performance. Under a tensile strain of 2.2%, the tensile stress can reach 2.2MPa. Compared with the existing metal electrode layer (almost no data from the tensile test), the long-term performance under cyclic contact is significantly improved, and the cyclic efficiency is higher.
[0084] Figure 7 This is a microscopic morphology of the low melting point alloy / polyvinyl alcohol composite material prepared in this embodiment. It can be seen from the figure that the hydroxyl functional group of the polymer material (polyvinyl alcohol) can form hydrogen bonds with the spontaneous oxidation surface of the low melting point alloy, which helps to form micro-nano-scale low melting point alloy droplets and make them evenly dispersed, and form microchannels between the low melting point alloy droplets, thereby constructing a stream vibration potential (SVP) model to enhance the energy conversion efficiency of cement-based composite materials.
[0085] Example 4
[0086] The difference between this embodiment and the embodiment 1 is that 25 parts of polyvinyl alcohol are weighed and added to deionized water, and the mixture is stirred at 90°C with constant temperature magnetic force until it is uniformly dissolved to obtain a polyvinyl alcohol solution. 0.8 parts of nano titanium dioxide are weighed and added to cement dry powder three times, and mechanically stirred at 400 rpm / min for 5 minutes at room temperature to obtain a uniformly mixed dry material mixture. The rest is the same as in the embodiment 1.
[0087] Example 5
[0088] The difference between this embodiment and embodiment 1 is that 25 parts of polyvinyl alcohol are weighed and added to deionized water, and the polyvinyl alcohol solution is obtained by constant temperature magnetic stirring at 90°C until it is uniformly dissolved. The low melting point alloy / polymer composite material is poured into a 1mm thick and 500mm 2 The electrode layer material is prepared by vibrating and compacting the material into a sheet-shaped silicone mold (which can enhance its output performance), and then drying the material at room temperature for 12 hours to obtain an electrode layer material. The rest is the same as in Example 1.
[0089] Example 6
[0090] The difference between this embodiment and embodiment 1 is that 25 parts of polyvinyl alcohol are weighed and added to deionized water, and the polyvinyl alcohol solution is obtained by constant temperature magnetic stirring at 90°C until it is uniformly dissolved. The low melting point alloy / polymer composite material is poured into a 0.5 mm thick and 200 mm 2 The electrode material is placed in a sheet-shaped silica gel mold, vibrated and compacted, and then dried at room temperature for 12 hours to obtain an electrode layer material. The rest is the same as in Example 1.
[0091] Example 7
[0092] The difference between this embodiment and embodiment 1 is that 0.4 parts of nano titanium dioxide is added to the sulphoaluminate cement dry powder three times, and mechanically stirred at a speed of 400 rpm / min for 5 minutes at room temperature to obtain a uniformly mixed dry material mixture. The rest is the same as in embodiment 1.
[0093] Example 8
[0094] The difference between this embodiment and embodiment 1 is that 25 parts of polyacrylamide are weighed and added to deionized water, and the solution is uniformly dissolved by constant temperature magnetic stirring at 90°C to obtain a polyvinyl alcohol solution. The low melting point alloy / polymer composite material is poured into a 0.5 mm thick and 200 mm 2 The electrode material is placed in a sheet-shaped silica gel mold, vibrated and compacted, and then dried at room temperature for 12 hours to obtain an electrode layer material. The rest is the same as in Example 1.
[0095] Comparative Example 1
[0096] (1) 0.4 parts of nano titanium dioxide were added to ordinary silicate P·I 52.5 cement powder in three times, and mechanically stirred at 400 rpm / min for 5 minutes at room temperature to obtain a uniformly mixed dry material mixture. 1.6 parts of water reducer were added to 60 parts of water, and magnetically stirred at 300 rpm for 3 minutes at room temperature, and then immediately poured into the dry material mixture, mechanically stirred at a uniform speed for 5 minutes, poured into a 40 mm*40 mm*10 mm plate mold, and vibrated until dense to obtain a cement matrix.
[0097] (2) The thickness is 1 mm and the area is 200 mm 2 The sheet-shaped stainless steel electrode layer material is inserted into the cement matrix so that it is located in the middle of the thickness of the cement matrix and is externally connected to a copper wire. After coating at room temperature for 24 hours, the specimen is cured in a curing box at 20±2°C and a relative humidity of 95% for 28 days to obtain a cement-based composite material with friction nano-power generation characteristics.
[0098] Comparative Example 2
[0099] (1) Add 10 parts of polyvinyl alcohol to deionized water, and stir the mixture with a magnetic stirrer at a constant temperature of 90° C. until the mixture is uniformly dissolved, thereby obtaining a polyvinyl alcohol solution. Keep the constant temperature at 90° C., add 0.1 parts of polyvinyl pyrrolidone to the polyvinyl alcohol solution, and stir the mixture with a magnetic stirrer until the mixture is uniformly dissolved, thereby obtaining a polyvinyl alcohol / polyvinyl pyrrolidone mixed solution.
[0100] (2) Maintaining a constant temperature of 90° C., adding indium tin bismuth alloy particles having a volume fraction of 0.1 of the polyvinyl alcohol / polyvinyl pyrrolidone mixed solution to the polyvinyl alcohol / polyvinyl pyrrolidone mixed solution, and stirring the mixture at a high speed of 3000 r / min for 10 min using a high-speed stirrer to uniformly disperse the low-melting-point alloy droplets in the polyvinyl alcohol / polyvinyl pyrrolidone mixed solution. The mixed solution was then allowed to stand for 8 h, and the supernatant was removed to obtain a low-melting-point alloy / polyvinyl alcohol composite material.
[0101] (3) Pour the low melting point alloy / polyvinyl alcohol composite material into a 1 mm thick and 200 mm area 2 The material was placed in a sheet-shaped silica gel mold, vibrated and compacted, and then dried at room temperature for 12 hours to obtain the electrode layer material.
[0102] (4) Pour 60 parts of water into the cement dry material, stir mechanically at a constant speed for 5 minutes, pour into a 40 mm*40 mm*10 mm plate-shaped mold, and vibrate until dense to obtain a cement-based composite material.
[0103] (5) Inserting the electrode layer material into the cement matrix so that it is located in the middle of the thickness of the cement matrix and externally connected to a copper wire. Then, after coating at room temperature for 24 hours, the specimen is cured in a curing box at 20±2°C and a relative humidity of 95% for 28 days to obtain a cement-based composite material with friction nano-power generation characteristics.
[0104] The output voltage and current, as well as the compressive strength of the cement-based composite materials prepared in the above-mentioned embodiments and comparative examples were measured, and the results are shown in Table 1.
[0105] Table 1 Output properties of cement-based composites
[0106] Output voltage(V) Output current (nA) Compressive strength(MPa) Example 1 45.3 125.6 50.72 Example 2 66.2 163.5 49.4 Example 3 75.5 191.7 50.18 Example 4 63 148.2 48.2 Example 5 87.6 203.4 46.45 Example 6 70.1 184.3 47.15 Example 7 47.2 123.8 56.88 Example 8 75.3 193.5 52.1 Comparative Example 1 28 100.3 39.3 Comparative Example 2 25.9 121.1 45.6
[0107] The output voltage of the composite material of the present invention can be controlled to be above 40V, while the output current is above 120nA, and the compressive strength is maintained above 46MPa, which can take into account mechanical properties, high energy output performance, and stable long-term performance.
[0108] Example 9
[0109] In this embodiment, in step (2), the dispersion temperature of the low melting point alloy is 80° C. and the stirring speed is 4000 r / min, which can form low melting point alloy droplets of about 80 nm.
[0110] Example 10
[0111] In this embodiment, based on the embodiment 1, the type of stabilizer is changed to poly(N-vinylamine), poly(N-vinylacetamide), or a mixture of polyvinylpyrrolidone and poly(N-vinylamine), and the mass ratio of the mixture is 1:1.
[0112] Embodiment 11
[0113] In this embodiment, based on the first embodiment, the type of nano material is changed to nano aluminum dioxide, nano barium titanate or nano strontium titanate.
[0114] Example 12
[0115] In this embodiment, based on the embodiment 1, the type of low melting point alloy is changed to bismuth-tin-lead-gallium alloy, gallium-indium alloy or bismuth-tin-lead-indium alloy, and the melting point is controlled within the range of 60-90°C.
[0116] Embodiment 13
[0117] In this embodiment, based on the first embodiment, the type of cement is changed to aluminate cement, phosphate cement, sulphoaluminate cement, magnesium oxychloride cement, or a mixed cement of ordinary Portland cement and the above cements in a mass ratio of 1:1.
[0118] According to tests, the cement-based composite materials of the present invention have high output performance and stable long-term performance under cyclic friction and load, and the difference in compressive strength relative to the original cement is kept within 15%.
[0119] Any matters not described in the present invention are applicable to the prior art.
Claims
1. A cement-based composite material with tribo-nanoelectricity generation characteristics, comprising a cement matrix and an electrode layer arranged in the cement matrix, characterized in that: The cement matrix is mixed with high dielectric constant nanomaterials to form a friction layer; the electrode layer is a low melting point alloy / polymer composite material, and the electrode layer is arranged in the friction layer.
2. The cement-based composite material according to claim 1, characterized in that: The addition amount of the high dielectric constant nanomaterial is 0.1%-1.5% of the cement mass; The volume ratio of the low melting point alloy component to the polymer solution in the raw materials of the low melting point alloy / polymer composite material is 0.06-0.
2.
3. The cement-based composite material according to claim 1, characterized in that: The dielectric constant of the high dielectric constant nanomaterial is greater than 10, and is preferably at least one of nano titanium dioxide, nano aluminum dioxide, nano barium titanate or nano strontium titanate; The low melting point alloy is an alloy material with a melting point of 60-90° C., preferably at least one of indium tin bismuth alloy, bismuth tin lead gallium alloy, gallium indium alloy, and bismuth tin lead indium alloy; The polymer solution uses water as a solvent, and uses a polymer material that is soluble in water and can form a film, and a stabilizer that promotes the dispersion of a low-melting-point alloy as solutes.
4. The cement-based composite material according to claim 3, characterized in that: The polymer material is at least one of polyvinyl alcohol, polyethylene glycol, polyimide, hydroxymethyl cellulose or polyacrylamide polymer materials; The stabilizer is an N-vinylamide polymer, preferably at least one of polyvinyl pyrrolidone, poly(N-vinylamine), and poly(N-vinylacetamide); The cement in the cement matrix is at least one of ordinary Portland cement, sulphoaluminate cement, phosphate aluminate cement, aluminate cement, phosphate cement and magnesium oxychloride cement.
5. The cement-based composite material according to claim 1, characterized in that: The low melting point alloy in the low melting point alloy / polymer composite material is micro-nano-scale particles, and the low melting point alloy is wrapped with a polymer solution outside, and has a flow vibration potential SVP.
6. The cement-based composite material according to claim 1, characterized in that: The raw material composition and mass percentage of the cement matrix are: 200 parts of cement, 0.2-3 parts of high dielectric constant nanomaterial, 1.6-3 parts of water reducer, and 60 parts of water; The raw materials of the low melting point alloy / polymer composite material include a polymer solution component and a low melting point alloy component, wherein the polymer solution component is composed of 5-35 parts of polymer material, 0.05-0.2 parts of stabilizer, and 100 parts of deionized water in parts by weight; The low melting point alloy component is added according to volume fraction, and its volume ratio to the polymer solution component is 0.06-0.
2.
7. A method for preparing a cement-based composite material having friction nano-power generation characteristics, characterized in that: The preparation method comprises the following steps: (1) adding a polymer material to water, stirring it with a constant temperature magnetic force until it is uniformly dissolved at a dissolution temperature, and maintaining the constant temperature condition, adding a stabilizer thereto, stirring it with a magnetic force until it is uniformly dissolved, and obtaining a polymer solution; the dissolution temperature can promote the water-soluble polymer material to dissolve in water to form a uniform polymer solution; (2) maintaining a temperature higher than the melting point of the low-melting-point alloy, adding low-melting-point alloy particles to the polymer solution, allowing the low-melting-point alloy to reach its melting point, causing it to first melt into a liquid state in the polymer solution, and then stirring at a high speed to form uniformly dispersed micro droplets, stirring at a uniform speed until the low-melting-point alloy droplets are uniformly dispersed in the polymer solution, and the low-melting-point alloy droplets are micro-nano-sized; Subsequently, the uniformly dispersed polymer solution is allowed to stand at room temperature for a period of time. Due to hydrogen bonding between the polymer chain and the low-melting-point alloy, a state of the low-melting-point alloy droplets being coated with the polymer chain is formed, so that the low-melting-point alloy droplets coated with the polymer solution are fully precipitated, and the supernatant is removed to obtain a low-melting-point alloy / polymer composite material; (3) pouring the low melting point alloy / polymer composite material into a sheet-shaped silica gel mold, vibrating and compacting it, and then drying it at room temperature to obtain an electrode layer material; (4) adding the high dielectric constant nanomaterial to the cement dry powder at least twice, and mechanically stirring at a speed of 300-450 rpm / min for 2-5 minutes at room temperature to obtain a uniformly mixed dry material mixture; then adding the water reducer into the water, magnetically stirring at room temperature to make it uniform, and immediately pouring it into the dry material mixture, and then stirring it at a uniform speed for 5-10 minutes, pouring it into a plate-shaped mold, and vibrating it until it is dense to obtain a cement matrix; (5) inserting the electrode layer material into the cement matrix so that it is located in the middle of the thickness of the cement matrix, externally connecting a copper wire, and then coating and curing at room temperature to a specified age to obtain a cement-based composite material with friction nano-power generation characteristics.
8. The preparation method according to claim 7, characterized in that: In step (2), the high-speed stirring speed is 3000-4000 r / min, the stirring time is 5-10 min, and the temperature is 80-100° C.; The size of the sheet-like silicone film is: 0.5-2mm thick and 100-500mm in area. 2 ; The curing method in step (5) is: after coating for 24 hours, the specimen is cured in a curing box at 20±2° C. and a relative humidity of 95% for up to 28 days.
9. A cement-based composite material having triboelectric nanoelectricity generation characteristics obtained by the preparation method according to claim 7 or 8, characterized in that: The cement-based composite material has high output performance and stable long-term performance under cyclic friction and load.
10. The cement-based composite material according to claim 9, characterized in that: The hydroxyl functional groups of the polymer material form hydrogen bonds with the spontaneously oxidized surface of the low-melting-point alloy, which helps to form micro-nano-scale low-melting-point alloy droplets and make them evenly dispersed, and form microchannels between the low-melting-point alloy droplets, thereby constructing the flow vibration potential SVP model; The output voltage of the cement-based composite material can be controlled above 40V, while the output current is above 120nA, and the difference in compressive strength relative to the original cement is kept within 15%.